APPLYING BAKER’S REFRAMING STRATEGIES TO TEXTS TRANSLATED FROM ENGLISH INTO BAHDINI KURDISH - TAHA AMEDI , ZEEN SAEED; AL-RUBAI’I, ALYA M.H (Journal of Duhok University, 2023)
On the question of why applying narrative theory to translation, Baker (2006) postulated that narratives are dynamic entities, they are prone to change as people are exposed to new stories daily. Similarly, during the process of translation, original texts are rendered into other languages which make them liable to re-narration. Translators usually tend to reframe texts and put them into different frames based on their personal or cultural experiences. Baker’s reframing strategies include temporality, selective appropriation, labelling, and positionality. Even though there is a considerable amount of research on reframing strategies, there is a noticeable gap in research on the use of reframing strategies in Kurdish translated texts, not to mention the most used ones. The current paper is an attempt to investigate this use in Bahdini Kurdish translated texts and identify the most used ones in accordance with Baker’s (2006) narrative theory. The selected data were taken from four books, categorized into two different text types: two literary texts (novels), John Green’s The Fault in Our Stars and Adichie’s Purple Hibiscus, and two non-literary texts (books on psychology), John Gray’s Men are From Mars, Women from Venus, and Joseph Murphy’s The Power of Your Subconscious Mind. The main findings of this research were that translators used reframing strategies in both text types and the most used ones were selective appropriation and labelling. Moreover, it was also found that temporality played an important role in paving the way for the emergence of these strategies.